Carbon footprint assessment of residential buildings, a review and a case study in Turkey. (15th March 2022) - Atmaca, Adem; Atmaca, Nihat
Abstract: Residential and commercial buildings consume around 40% of the total energy of the world. The building sector is also responsible for 30% of the global greenhouse gas emissions. There is an urgent need to assess the environmental carbon footprint (CFP) of global building industry. This study reviews the related studies and calculates the CFP of a residential building constructed in Turkey by considering the type of construction materials, energy consumption habits, maintenance and demolition stages in a 50 year of life cycle. The CFP of a common type of residential building constructed in Turkey found to be 48.87 kgCO2 eq/m 2 /year. The CFP of structural elements used during the construction phase has been calculated to be 6.94 kgCO2 eq/m 2 /year, which is about 14.21% of the total footprint. It is investigated that; the operational stage is the foremost contributor, representing 64.11% of CFP. The CO2 emissions have been decreased by 38.05% by the implementation of basic methods. Unlike other studies, this paper revealed that the CFP from transportation of habitants is 6.5% more than the construction stage contributing 15.13% of overall emissions. The comparative studies of constructions in different countries show that CFP significantly depend on the behavioral factors of citizens of a country and the system boundaries selected. The results exposed that the effects of transportation should not be disregarded in the future studies. Graphical abstract: Image 1 Highlights: The total life cycle CFP of the building found to be 48.87 kgCO2 eq/m 2 /year. The CFP of construction materials is calculated to be 6.94 kgCO2 eq/m 2 /year. CFP from transportation of habitants is 6.5% more than the construction stage contributing 15.13% of overall emissions. The daily energy use of the habitants is the main contributor to the CFP, representing the 64.11% of CFP. The CFP of the building has been decreased by 38.05% by the implementation of low-carbon strategies.